Carotenoids in the needles of Pinus nigra as bioindicators of the degree of pollution in the Atmospheric air of Skopje - Jordanov, Saško; Mulev, Milto; Melovski, Ljupčo; Derlieva, Lidija (Macedonian Journal of Ecology and Environment, 1997)
The content of the carotenoids was determined in the two year old needles of Black pine (Pinus nigra) in the course of the vegetational year 1993/94. The samples were collected once per month at three local areas in Skopje: Aerodrom, Chair and Panorama, which have different degrees of air pollution. At these measuring points The Republic’s Hydro - metheorological Institute - Skopje and The City Institute for Health Prevention-Skopje, are continuously following the concentration of smoke in the atmospheric air over a longer’ period of time. On the basis of the obtained data from these institutes, the highest yearly average value of smoke concentration over’ a 10 - year period was confirmed in the Aerodrom measuring point. In the areas of Aerodrom and Chair which were characterized by higher yearly average values of smoke concentration, higher yearly average values were registered in the carotenoids content in needles of Black pine (Pinus nigra) in comparison with the Panorama area.